Wujud Ajaran Tri Hita Karana pada Interior Pura Agung Jagad Karana Surabaya - Wahana, Ni Putu Purnasari Dewi; Sari, Sriti Mayang; Rakhmawati, Anik (Intra, 2015)
Living in peace, harmony, and prosperity is definitely every human desire.Â There are three factors in determining happiness in Hinduism, which are having a harmony to God, to other human being, and to nature, in which these are known as Tri Hita Karana. Tri Hita Karana theory is connected to Tri Mandala concept, which consists of Utama Mandala, Madya Mandala, and Nista Mandala. This research is aimed to further explore the concept of Tri Hita Karana, in the context of Agung Jagad Karana Temple in Surabaya. The methods that will be used in this research are both qualitative descriptive method. As a result, Agung Jagad Karana Temple in Surabaya has fully attained the concept of Tri Mandala, thus Tri Hita Karana theory has also been achieved in each of the templeâ€™s architecture and interior, which means that it has also formed a balance relationship between human and God, human and other human being, as well as human and nature.